Income support for the unemployed : issues and options - Vodopivec, Milan (Washington, D.C. : World Bank, 2004)
Represents one effort of the World Bank's Human Development Network to analyze the effects of labor market policies and programs. It will be of interest to policymakers and development practitioners seeking to introduce or improve income support programs for the unemployed.
Includes bibliographical references (p. 187-207)and index.
oif 01/04/15
Loan
Keywords: Unemployment insurance; Supplemental unemployment benefits; Severance pay; Public works